Development of Smart Food Waste Filter Using Eco-Friendly Materials with Sensor - Abdullah, Mohamad Najibbuddin; Rosli, Mohd Arif; Abdul Rahman, Mohd Fahmi (Progress in Engineering Application and Technology, 2022)
The study aims to the effectiveness of coconut husk, activated carbon, and rice straw filtering greywater produced from the domestic house. This food waste filter is equipped with an IR sensor system that can assist in maintenance, i.e., filter cleaning after trapped waste fills the filter space and is installed under the sink. The properties used for this study to evaluate the filter's effectiveness are physical, chemical, and biological properties. These parameters include the BOD5, COD, pH, turbidity, and total suspended solids. The method used to examine the greywater is based on the APHA, 2012 method. The pre and post-filtration are observed to evaluate the characteristics of greywater. The percentage removal of impurities for these parameter is turbidity 96%, COD 68%, suspended solid 96% and BOD5 is 48.6%. While for pH value, the value may be varying because the wastewater generation varies by location, and its composition is determined by cooking activities, kitchen dishwashing, hand soap, and vegetable or fruit washing in the kitchen. The substances used as filter media contribute to the effectiveness of reducing the rate of impurities in greywater. The IR sensor used has detected the presence of solid waste trapped in this food waste filter on the third day of use. Further studies can be done to improve food waste filters in terms of size and design, reduce ammonia in wastewater, and the limit usage of filter materials.